2007
DOI: 10.5194/nhess-7-741-2007
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami propagation modelling – a sensitivity study

Abstract: Abstract. Indian Ocean (2004)Tsunami and following tragic consequences demonstrated lack of relevant experience and preparedness among involved coastal nations. After the event, scientific and forecasting circles of affected countries have started a capacity building to tackle similar problems in the future. Different approaches have been used for tsunami propagation, such as Boussinesq and Nonlinear Shallow Water Equations (NSWE). These approximations were obtained assuming different relevant importance of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 12 publications
3
84
0
1
Order By: Relevance
“…Delft3D-FLOW internally converts Manning's roughness values to a depth-dependent Chézy roughness for all computations (Deltares, 2014b). Previous research has demonstrated the Manning's roughness formulation is appropriate for simulation of the ocean bed boundary condition hydraulic losses and that this parameter has some effect on simulation results of long-wavelength wave propagation (Dao and Tkalich, 2007;Knighton and Bastidas, 2015;Sraj et al, 2014).…”
Section: Flow Bottom Frictionmentioning
confidence: 99%
“…Delft3D-FLOW internally converts Manning's roughness values to a depth-dependent Chézy roughness for all computations (Deltares, 2014b). Previous research has demonstrated the Manning's roughness formulation is appropriate for simulation of the ocean bed boundary condition hydraulic losses and that this parameter has some effect on simulation results of long-wavelength wave propagation (Dao and Tkalich, 2007;Knighton and Bastidas, 2015;Sraj et al, 2014).…”
Section: Flow Bottom Frictionmentioning
confidence: 99%
“…In tsunami models the bottom friction components f x and f y are usually expressed in terms of the fluxes M, N and of a friction coefficient C f , which in turn can be given in terms of the Manning's roughness coefficient n (see Satake and Tanioka, 1997;Dao and Tkalich, 2007), the final result being…”
Section: Background Theorymentioning
confidence: 99%
“…The models have also been implemented widely by different researchers to simulate tsunami propagations and wave heights in Pacific, Atlantic, and Indian Oceans, with zoom in at particular areas of Caribbean, Japanese, Russian, South China, Mediterrenean seas and Gulf of Cadiz (Yalciner et al, 2000(Yalciner et al, , 2001(Yalciner et al, , 2002Baptista et al, 2003;Zahibo et al,2003;Yalciner, 2004;Annunziato, 2007;Dao and Tkalich, 2007;Yolsal et al, 2007;Franchello ,2008;Franchello and Krausmann, 2008;Kaabouben et al, 2008;Dao, et al, 2009;Franchello, 2010;Yolsal and Taymaz, 2010;Cruz et al, 2011;Ulutas, 2011). Although the SWAN (Mader, 1988) model was adapted to the TEWS, which is a part of GDACS, all included models might be used manually in order to predict tsunami arrival times and maximum heights.…”
Section: Post-event Analysismentioning
confidence: 99%